Discovery of an Environmentally Friendly Water-Soluble Luminous Material with Interstitial Site Occupancy; ACS Sustainable Chemistry and Engineering; Vol. 9, iss. 7 - Wang Jinyu; Lang Tianchun; Fang Shuangqiang; Khan Tao; Cai Mingsheng; Wang Mingguang; Cao Shixiu; Peng Lingling; Bitao Liu; Polisadova E. F. Elena Fyodorovna; Yakovlev A. N. Aleksey Nikolaevich (2021, 2021)
Title screen